HISTORICAL CONCEPTION ACCORDING TO THE NATURAL MALAY TAFSIR OF TURJUMAN AL-MUSTAFAD: A TAFSIR STUDY OF THE NUSANTARA - M. Irfan Farraz Haecal; Dadan Rusmana (Al-Risalah, 2022)
The purpose of this research is to discuss the conception of history, used by Shaykh 'Abdu al-Rauf al-Singkili in interpreting verses that have historical content in the Tafsir of Turjuman al-Mustafid. This research uses a Qualitative approach through literature-based methods. The results of this study show that the Conceptual Historicality used by Shaykh Abdu al-Rauf al-Singkili is a concept of Historical Law, focusing on a series of events that explain the state of the past as an object of empirical study, and as a comparison (Ibrah) to the present, in it has a simple nature, unique elegance., and is fixed. This research recommends further research related to the conception of history in this Tafsir of Turjuman al-Mustafid in view of Historical Science with an approach to the Islamic science group.